The first complete chloroplast genome of a major mangrove species Sonneratia alba Sm. and its implications on conservation efforts. Issue 2 (3rd July 2018) - Yu, Tianhui; Hinsinger, Damien Daniel; Strijk, Joeri Sergej; Wee, Alison Kim Shan
Abstract: Sonneratia alba Sm. is one of the most widely distributed mangrove species worldwide. In this study, the whole chloroplast genome of S. alba was assembled for the first time not only in Sonneratia, but also for a member of the mangrove plant community. The total chloroplast genome was 153, 061 bp in length, with a large single copy (LSC) region of 87, 226 bp and a small single copy (SSC) region of 18, 033 bp, separated by two inverted repeats (IRs) regions of 23, 901 bp. The overall GC content was 37.3%, and 43.1%, 35.4%, and 31.1% in the IRs, LSC, and SSC regions, respectively. It contained 106 genes, including 79 coding genes, 24 tRNA genes, and four rRNA genes. A phylogenetic analysis confirmed that S. alba was clustered with Trapa maximowiczii within the family Lythraceae.